“For What Purposes are they Suffering and for What are they Living”. Again on the Teleological Paradigm of Chekhov’s World (Proceedings of Southern Federal University. Philology, 2020)
It is considered the paradigm of teleological models, attempts to answer the eternal question about the meaning and purpose of existence in Chekhov’s. It is introduces the concepts of «anchor model» (justification of life by simplifying it by forcing the introduction of meaning), «model vector» (general aspiration towards meaningful life) and «field man» (according to Chekhov’s ideology, a true sage walking between the poles «there is a sense» and «there is no sense»).Key words: teleological model, meaning of existence, goal, model «anchor», model «vector», «field man», Chekhov.DOI 10.18522/1995-0640-2020-2-43-50